2022
DOI: 10.1101/2022.11.04.22281944
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repeatability and timing of tropical influenza epidemics

Abstract: Much of the world experiences influenza in yearly recurring seasons, particularly in temperate areas. These patterns can be considered repeatable, occurring predictably and consistently. In tropical areas, including southeast Asia, this consistency is less conspicuous. This study aimed to assess repeatability of influenza in Vietnam. A mathematical model was developed incorporating periods of increased transmission, and fit to data from sentinel hospitals throughout Vietnam as well as four temperate locations.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…4D). A single influenza peak per year does not guarantee that peak timing is repeatable or consistent 14 . In addition, the peak timings and the periodic signals are not consistent across subtypes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4D). A single influenza peak per year does not guarantee that peak timing is repeatable or consistent 14 . In addition, the peak timings and the periodic signals are not consistent across subtypes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of ILI patients among total outpatient visits per day (%ILI) in each clinic from January 1, 2010 to December 31, 2019 is used as the primary data type in the analysis. The %ILI time series for each clinic was detrended to an ILI ζ -score (“zeta” score) to remove long-term decreasing trends seen in seven clinics 13,14 (see S1 Text). Daily data were detrended using the ζ -score for each clinic, and then the arithmetic mean among all clinics reporting that day was calculated to get an aggregated ILI time series.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We adjusted the transmission levels in the model for future projections based on influenza dynamics in the US. Seasonal wintertime forcing in transmissibility was introduced starting in season 2023-2024, where transmission increases by up to 20 percent in a sinusoidal curve between October and February, estimated from influenza transmission during winter in the northeastern US (46). The baseline transmission rate after March 1, 2023 was assumed to be the mean of the transmission parameter throughout the entire third year.…”
Section: Projecting Future Disease Burdenmentioning
confidence: 99%
“…The absence of winter in tropical regions makes the yearly patterns of influenza and influenza-like illness (ILI) less seasonal and less predictable 9. Thus far, it has been found that influenza in tropical regions shows lower variation in incidence,10 11 higher variation in epidemic timing10 12 and different periodicities geographically,10 13–18 making it difficult to forecast periods of high incidence. Although some studies in tropical areas have shown associations between climate or environmental factors and influenza transmission,11 19–23 this relationship remains elusive16 24 25 and caution is needed in interpreting these results and drawing inferences on a ‘typical’ tropical influenza season.…”
Section: Introductionmentioning
confidence: 99%